Projection - Green, Risa (Soho Teen, 2013)
"In ancient Rome, it was whispered that the great philosopher Plotinus could project his soul into another human being in a ritual that hinged on a kiss. In present-day Delphi, California, the sole remaining guardians of the Plotinus Ability hide in plain sight as members of the exclusive Oculus Society--until their leader, Octavia Harris, is killed in her own home. With no leads on the case, Octavia's daughter, Gretchen, vows to find her mother's murderer at any cost"--